Exploring the economic contribution and visibility of women in UK agriculture - Dunne, Chloe (2025)
While the overall number of people occupied within the agriculture sector falls, the UK and other developed countries has witnessed a rise in the proportion of women occupied within the industry. Insights from cross-disciplinary research suggests that differences between the roles and performance of men and women are found to occur; with women substantially underrepresented as farm holders and often associated with lower visibility roles and contributions than their male counterparts. Yet, research from the field of economics lags and the area has received little attention from policy and public bodies.